1981
DOI: 10.1093/ajcp/75.4.629
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Transfusion Reaction due to Anti-Kell Undetectable in Low-ionic-strength Solutions

Abstract: Low-ionic-strength solution (LISS) reagents and methodologies have become popular in recent years in hospital transfusion service laboratories for alloantibody detection and compatibility testing of blood recipients. It has been the experience with all other hemagglutination technics that some examples of alloantibodies unpredictably fail to react. Such is the case with this patient's alloantibody with respect to LISS. The patient had a significant hemolytic transfusion reaction due to Kell incompatibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
3
6
1
Order By: Relevance
“…The results obtained demonstrate higher absorbance values in each category of agglutination grading for anti-K than for any other antibody specific ity tested. This finding suggests enhanced binding of anti-K to red cells relative to that of other antibodies and contrasts with the findings in conventional LISS-AGT of im paired reactivity of anti-K [10,11].…”
Section: Discussioncontrasting
confidence: 95%
“…The results obtained demonstrate higher absorbance values in each category of agglutination grading for anti-K than for any other antibody specific ity tested. This finding suggests enhanced binding of anti-K to red cells relative to that of other antibodies and contrasts with the findings in conventional LISS-AGT of im paired reactivity of anti-K [10,11].…”
Section: Discussioncontrasting
confidence: 95%
“…lb) show that there is no increased bind ing in LISS. This confirms serological inves tigations [13][14][15] which showed that the stan dard LISS technique does not provide opti mum conditions for the binding of these antibodies. Indeed, Hughes-Jones et al [2] in the original work on LISS suggested that some antibodies might bind at a reduced rate in LISS.…”
Section: Antiserasupporting
confidence: 83%
“…This problem was overcome in a study of Low and Messeter [3] who claimed that all clini-ported ranging from 4-fold [11] to 1,000-fold [2], It should be noted that the latter figure referred to a final molarity ofO.Ol M which is unsuitable for routine use because of the increased incidence of false positives. Since the LISS technique is now widely used in the crossmatch, it was decided to reinvestigate the rate of antibody binding using a sensitive test for cell-bound IgG which has been re cently developed [12], There have been re ports of failure of the standard LISS test to detect Kell antibodies [13,15], though Voak et al [15] have shown they may be optimally detected in a modified LISS test which in cludes an increase in the ratio of serum to packed cells to 40:1 in comparison to the standard 20:1, and doubles the volume of AHG reagent added. Stratton [16] has pre viously investigated the effect of serum/cell ratio on antibody detection in solutions of varying ionic strength and concluded that the ratio is of considerable importance.…”
mentioning
confidence: 99%
“…The detection of weak anti-K does present certain difficulties: the antibody is better detected in NISS IAT tests (Molthan & Strohm, 1981;Merry et al, 1984). Early LISS IAT tube tests used one volume of 5% red cells suspended in LISS mixed with one volume of serum (serum to red cell concentration ratio 20 : 1) (Voak et al, 1980).…”
Section: Discussionmentioning
confidence: 99%